PERAN LINGKUNGAN FISIK, MOTIVASI DAN DISIPLIN KERJA DALAM MEMBERI DAMPAK PADA KINERJA PEGAWAI - Wijayanti, Intan Aprillia; Dewi, Dian Ayu Liana (LPPM STIE Muhammadiah Bandung, 2025)
The public health center is a government health institution that plays a role in maintaining public health. Realizing an organization's vision and mission requires superior and high-quality human resources. This study was conducted to provide information on the relationship between the physical environment, motivation, and work discipline with the performance of employees at the UPT Puskesmas Gunem, Rembang Regency. This study uses a quantitative approach as the chosen method. The type of data is subject data and the source of data is primary data. The population in this study involves 40 officers. The technique involved in the sample selection is a saturated sample. The questionnaire is the tool used as a data collection technique in this study. Instrument testing, multiple linear regression testing, hypothesis testing, and determination testing serve as data analysis techniques. This study has findings where the physical environment variable has a negative insignificant relationship with employee performance, while the motivation and discipline variables have a partially positive insignificant relationship with employee performance. The findings of the determination test show that the three variables used in the research study only contribute 38.6%, while the remaining portion is caused by other factors not included in this study.